Community Relations Strategy at PT Tirta Investama (Danone-Aqua) in Building a Social License to Operate through a Community Empowerment-Based Agroforestry Program - Vira Indah Nugraini; Maylina Cahyaningtyas; Pramudya Ibnu Subrata (The Indonesian Institute of Science and Technology Research, 2026)
This study develops a conceptual framework explaining how community relations strategies contribute to building a social license to operate (SLO) through an agroforestry-based community empowerment program implemented by PT Tirta Investama (Danone-Aqua). The rapid growth of Indonesia’s bottled water industry has raised concerns regarding environmental impacts and unequal access to water resources. Consequently, companies in natural resource-based sectors must not only comply with formal regulations but also secure social acceptance from local communities. This study adopts a conceptual approach using a systematic literature review, integrating perspectives from public relations (PR), stakeholder theory, legitimacy theory, and SLO. Data were collected from scientific journals, academic books, institutional reports, and company documents related to community relations and sustainability practices. The analysis employs concept mapping and theoretical synthesis to examine relationships among community engagement, dialogic communication, trust building, social legitimacy, and public acceptance. The findings indicate that community relations strategies emphasizing two-way communication, transparency, and active participation enhance community involvement, strengthen trust, and foster social legitimacy. Agroforestry-based empowerment programs function as collaborative mechanisms that generate shared value for both companies and communities. Thus, community relations serve not only as a communication strategy for reputation building but also as a critical mechanism for obtaining and sustaining SLO, ultimately supporting long-term operational sustainability.